Grain quality indicators and their phenotypic variability of ancient varieties of Triticum aestivum in the mountains of Uzbekistan - FARID RUZIYEV; IBROHIM DJABBAROV; SADOKAT OLIMJONOVA; ULUGBEK NIYOZOV; SIROJIDDIN UROKOV; DILAFRUZ ISHANKULOVA; UMIDJAN BAKHADIROV (Society for Indonesian Biodiversity, 2023)
Abstract. Ruziyev F, Djabbarov I, Olimjonova S, Niyozov U, Urokov S, Ishankulova D, Bakhadirov U. 2023. Grain quality indicators and their phenotypic variability of ancient varieties of Triticum aestivum in the mountains of Uzbekistan. Biodiversitas 24: 5995-6001. Today, creation of varieties of agricultural crops that are resistant to adverse environmental factors and produce stable crops under the influence of stress factors has become one of the most important issues in the world. In the following years, scientific and research work is being carried out on the wide use of the diversity of its genetic resources in the creation of new varieties of wheat (Triticum aestivum L.). In this regard, there are opportunities to use wild, semi-wild and ancient local forms of wheat with high protein and high gluten content to create varieties that meet modern production requirements. Therefore, it is important to evaluate the quality indicators of ancient varieties and the degree of phenotypic variation in the selection of wheat varieties that are resistant to adverse environmental factors, fertile and high-quality. This research work, aimed at researching ancient wheat varieties cultivated by the people living in the mountainous regions of Uzbekistan for many years. According to the research results, the grain quality indicators (grain hardness, diameter of grains, grain quality indicators, rheological properties, etc.) of the ancient wheat varieties distributed in the mountain regions are different. According to the results of the experiment, the grain hardness of the studied ancient wheat varieties is 73-82 µm, grain diameter 2.65-2.71 mm, hectolitre of weight 818.2-838.1±8.7 g/L, vitreousness 62.2-70.3%, gluten content in grain 31.5-34.6%, sedimentation index 64.4-77.2 mL. It was also observed that the phenotypic variability of the quality indicators was different in the wheat varieties that were the object of the study. Differences in the grain quality indicators of ancient wheat varieties are explained by the different effects of climatic parameters, abiotic and biotic factors in the regions where wheat grows. The information presented in the article provides an opportunity to select ancient wheat varieties distributed in the mountainous regions of Uzbekistan as starting sources for the creation of varieties with high nutritional value, resistant to adverse factors.